Fabrication of paper-based analytical devices using a PLA 3D-printed stencil for electrochemical determination of chloroquine and escitalopram - Silva, Martin K. L. [UNESP]; Sousa, Guilherme S. [UNESP]; Simoes, Rafael P. [UNESP]; Cesarino, Ivana [UNESP] (Springer Nature, 2022)
In recent years, the use of prescribed and non-prescribed drugs has increased. Therefore, advances in new technologies and sensors for detecting molecules in natural environments are required. In this work, a 3D-printed polylactic acid stencil is used to fabricate paper-based analytical devices (ePADs). Herein, we report the use of carbon-based lab-manufactured conductive ink for the fabrication of sensors towards the detection of chloroquine and escitalopram. For each batch, eight ePADs were successfully fabricated. Firstly, the fabricated sensors were evaluated morphologically by scanning electron microscopy and electrochemically by cyclic voltammetry and electrochemical impedance spectroscopy experiments. The sensors displayed a well-defined voltammetric profile in the presence of the redox couple, when compared to a commercial carbon screen-printed electrode. Differential pulse voltammetry conducted the detection of chloroquine and escitalopram with detection limits of 4.0 and 0.5 µmol L−1, respectively. The ePADs fabricated using the 3D stencil are here presented as alternatives for the fabrication of electrochemical analytical devices.
Keywords: 3D-printing; Chloroquine; Conductive ink; Electrochemical paper-based analytical devices (ePADs); Escitalopram